Studi instrumen gas analyzer inlet KILN 5W1A50A1 untuk pengukuran kadar oksigen di KILN pada PT. Semen Padang (Study of the KILN 5W1A50A1 inlet gas analyzer instrument for measuring oxygen levels at KILN at PT. Semen Padang ) - Nila Yulita; - Asrizal; Zulhendri Kamus (Department of Physics – Universitas Negeri Padang UNP, 2018)
Oxygen has an important role in the process of burning cement and producing Carbon Monoxide. The oxygen content can be measured using a Gas Analyzer. At PT. Semen Padang has a Gas Analyzer but information about instruments, data and analysis and the use and constraints of the Gas Analyzer are still lacking. To answer this promblem researchers are interested in conducting further research. This research includes descriptive research, namely research that aims to describe or explain an object's variables. measurement results obtained from the measurement results using a Gas Analyzer. the measurement results obtained will be analyzed statistically and graphically. the measurement results are analyzed by data in one day, one week, one month and for 6 months. Based on the results of data analysis it can be seen that the oxygen gas content of the measurement results is still in the range used.